2017
DOI: 10.1098/rsob.170104
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase: a therapeutic target in intestinal diseases

Abstract: Adenosine monophosphate (AMP)-activated protein kinase (AMPK), a highly conserved energy sensor, has a crucial role in cardiovascular, neurodegenerative and inflammatory diseases, as well as in cancer and metabolic disorders. Accumulating studies have demonstrated that AMPK activation enhances paracellular junctions, nutrient transporters, autophagy and apoptosis, and suppresses inflammation and carcinogenesis in the intestine, indicating an essential role of AMPK in intestinal health. AMPK inactivation is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 175 publications
(219 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, the Bio-Eth/streptavidin-agarose pull-down experiment demonstrated the direct interaction of Eth/AMPK ( Figures 4G-L). AMPK acts as tumor suppressor to inhibit carcinogenesis, and promote apoptosis (Sun and Zhu, 2017). We showed that in 75/143 (52%) BCs, pAMPK was lower in tumor samples than in normal breast tissues ( Figures 5C, D).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the Bio-Eth/streptavidin-agarose pull-down experiment demonstrated the direct interaction of Eth/AMPK ( Figures 4G-L). AMPK acts as tumor suppressor to inhibit carcinogenesis, and promote apoptosis (Sun and Zhu, 2017). We showed that in 75/143 (52%) BCs, pAMPK was lower in tumor samples than in normal breast tissues ( Figures 5C, D).…”
Section: Discussionmentioning
confidence: 86%
“…Tight junctions are developed during intestinal stem cells differentiating into epithelial cells . Nutraceutical factors or therapeutic strategies that enhance intestinal epithelial differentiation can improve gut epithelial barrier function and health …”
Section: Introductionmentioning
confidence: 99%
“…[7] Nutraceutical factors or therapeutic strategies that enhance intestinal epithelial differentiation can improve gut epithelial barrier function and health. [8] Accumulating evidence supports the beneficial effects of dietary polyphenols in preventing leaky gut. [9,10] Dietary intake of polyphenol-rich food, such as green tea, grapes, and berries, strengthens intestinal barrier integrity and the formation of tight junctions [11] in an energy-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine monophosphate activated protein kinase (AMPK) plays a multiple beneficial role in gut health; it improves barrier function and intestinal absorption, suppresses colorectal carcinogenesis, and reduces intestinal inflammation [41]. The deactivation level of AMPK pathways reduces during GI cancer and as a result enhances tumor progression and reduces apoptotic pathway activation [42]. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and mitogen-activated protein kinase (MAPK) pathways reduce during GI cancer, potentially leading to enhanced cell cycle progression, oxidative stress, and cellular proliferation [43,44].…”
Section: Impact Of Gastrointestinal Cancer On Selected Pathwaysmentioning
confidence: 99%